局限期小细胞肺癌治疗新格局： 从传统放化疗到精准治疗的新进展. - HAN, Jingwen; DAI, Keyao; MENG, Zixi; HUANG, Jun (Chinese Journal of Lung Cancer, 2026)
Limited-stage small cell lung cancer (LS-SCLC) is a highly aggressive malignancy with a poor prognosis. For a long time, the standard first-line treatment has been Etoposide plus Platinum-based chemotherapy combined with concurrent thoracic radiotherapy; however, most patients still face recurrence and drug resistance. This article systematically reviews major recent advances in the field, aiming to illustrate the new paradigm shifting from conventional chemoradiotherapy toward precision-integrated therapy. Radiotherapy techniques continue to be optimized, and the value of surgery has been reaf- firmed in rigorously selected early-stage patients; immunotherapy has achieved a milestone breakthrough, with the ADRIATIC trial demonstrating that consolidation therapy with Durvalumab after chemoradiotherapy significantly extends median overall survival (55.9 vs 33.4 months); meanwhile, targeted therapies based on molecular subtyping also show promise. This paper clarifies the optimized directions of multimodal treatment strategies, emphasizes the guiding significance of molecular subtyping and biomarkers in individualized therapy, with the aim of providing reference for clinical practice, offering a framework for future research, and ultimately improving the survival outcomes of LS-SCLC patients as a whole.